Realism vs. Neoliberalism and Constructivism: Main Points of Debate - Y. V. Borovsky; P. A. Gvozdev (Vestnik MGIMO-Universiteta)
Abstract: Following the collapse of the bipolar world realist approaches were placed under close scrutiny by neoliberals and constructivists. The legacy of the realist school actually became an object of numerous attacks, which were undertaken to demonstrate its discrepancy with new international realities. In the course of sharp debates proponents of realism managed to show the weakness of neoliberal argumentation and, further, to testify that a number of high-sounding neoliberal theories are poorlygrounded. At the same time, realism’s supporters proved themselves to be incapable of defeating constructivists. The new opponents persuasively revealed the apparent though neglected earlier controversy between the basic materialist assumptions of the realist school and the not entirely materialist tool of their reflection in the international relations, i.e. the concept of power. Only after a time realists managed to find some credible theoretical ground and make first effective steps towards building a consistent system of counterarguments against constructivism. However, ‘the constructivist assault’ caused a profound review of the realist theoretical and practical apparatus. Among currently relevant applied propositions of the school we should name assumptions of statism, of anarchy, of the significance of the power factor (while recognising the dual nature of power in international relations) as well as the ‘relative gains problem’.